Comportamiento agronómico de cuatro híbridos de pepino (Cucumis sativus L) bajo las condiciones edafoclimáticas del campus politécnico de la ESPAM - Hidrovo Zambrano, Ángela Victoria (2016)
This research was carried out from September to November of 2015 at ESPAM-MFL Polytechnic Campus, located in “El Limón” Canton of Bolívar Manabí-Ecuador, with the aim of evaluating the agronomic performance of four hybrids of cucumber (Cucumis sativus L), Darlington, Diamond, Humocaro and Intimidator. For the establishment of the crop, a four repetitions design at random was used, blocking in repetitions the hypothetical natural soil fertility heterogeneity. Yield variables analyzed statistically were number of fruits per plant and per hectare, length, diameter and weight of fruit, and yield t/ha, besides complementary variables were analyzed such as days to germination, days to flowering, days to fruiting, vegetative cycle, level presence of insects and pathogens. The results of the statistical analysis determined that the hybrid Darlington showed the best result for variables number of fruits per plant with an average of 7.32, number of fruits per hectare (146,400) and weight yield with 54.33 t/ha. Likewise, this material lasts the longest with a vegetative cycle of 73 days. These qualities contributed to improve the cost of crop production, reaching a profit of $ 3669,88 per hectare and a marginal rate of return of 55,79 %.